2013
DOI: 10.1088/1367-2630/15/2/025042
|View full text |Cite
|
Sign up to set email alerts
|

Near-monochromatic high-harmonic radiation from relativistic laser–plasma interactions with blazed grating surfaces

Abstract: Intense, femtosecond laser interactions with blazed grating targets are studied through experiment and particle-in-cell (PIC) simulations. The high harmonic spectrum produced by the laser is angularly dispersed by the grating leading to near-monochromatic spectra emitted at different angles, each dominated by a single harmonic and its integer-multiples. The spectrum emitted in the direction of the third-harmonic diffraction order is measured to contain distinct peaks at the 9th and 12th harmonics which agree w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…To this aim, the blaze angle is chosen in order that the incident light is locally reflected in the same direction as the diffraction angle. In the high intensity regime, blazed gratings have been used to optimize high harmonic generation 42,43 (section IV).…”
Section: Source Optimization With Blazed Gratingsmentioning
confidence: 99%
“…To this aim, the blaze angle is chosen in order that the incident light is locally reflected in the same direction as the diffraction angle. In the high intensity regime, blazed gratings have been used to optimize high harmonic generation 42,43 (section IV).…”
Section: Source Optimization With Blazed Gratingsmentioning
confidence: 99%
“…Blazed diffraction grating is a special kind of grating target, which is widely used in optical spectrum measurement to enhance the spectrum brightness along a controllable direction [39]. In previous work, both numerical simulations and experiments have demonstrated that selected harmonics can be obtained from relativistic laser-plasma interactions with blazed grating targets when an appropriate blaze condition is satisfied, which provides a potential route to achieve near-monochromatic, short pulsed XUV radiation [29,40]. In this paper, we revisited the HHG from blazed grating targets and show that such targets cannot only select the specific harmonics in a specific direction through grating diffraction, but also enhance the maximum detectable harmonic order and intensity in a predetermined direction.…”
Section: ( )mentioning
confidence: 99%
“…9,10 In this paper, we report on the emission of multi-MeV electron bunches accelerated along the target surface during short pulse laser-interaction with a grating target. Experimental results have been obtained in conditions of relativistically strong intensity (> 10 19 W/cm 2 ) and ultrahigh contrast (10 12 ) laser pulses.…”
Section: Introductionmentioning
confidence: 99%